Prediction of Long-Term Recovery From Disability Using Hemoglobin-Based Models: Results From a Cohort of 1,392 Patients Undergoing Spine Surgery - Briguglio, Matteo; Perazzo, Paolo; Langella, Francesco; Crespi, Tiziano; De Vecchi, Elena; Riso, Patrizia; Porrini, Marisa; Scaramuzzo, Laura; Bassani, Roberto; Brayda-Bruno, Marco; Banfi, Giuseppe; Berjano, Pedro (Frontiers in Surgery, 2022)
Hemoglobin and its associated blood values are important laboratory biomarkers that mirror the strength of constitution of patients undergoing spine surgery. Along with the clinical determinants available during the preadmission visit, it is important to explore their potential for predicting clinical success from the patient’s perspective in order to make the pre-admission visit more patient-centered. We analyzed data from 1392 patients with spine deformity, disc disease, or spondylolisthesis enrolled between 2016 and 2019 in our institutional Spine Registry. Patient-reported outcome measure at 17 months after surgery was referred to the Oswestry disability index. High preoperative hemoglobin was found to be the strongest biochemical determinant of clinical success along with high red blood cells count, while low baseline disability, prolonged hospitalization, and long surgical times were associated with poor recovery. The neural network model of these predictors showed a fair diagnostic performance, having an area under the curve of 0.726 and a sensitivity of 86.79%. However, the specificity of the model was 15.15%, thus providing to be unreliable in forecasting poor patient-reported outcomes. In conclusion, preoperative hemoglobin may be one of the key biomarkers on which to build appropriate predictive models of long-term recovery after spine surgery, but it is necessary to include multidimensional variables in the models to increase the reliability at the patient’s level.